Roots of the Invasive Species Carduus nutans L. and C-acanthoides L. Produce Large Amounts of Aplotaxene, a Possible Allelochemical - Silva, Ferdinando M. L. [UNESP]; Donega, Mateus A.; Cerdeira, Antonio L.; Corniani, Natalia [UNESP]; Velini, Edivaldo D. [UNESP]; Cantrell, Charles L.; Dayan, Franck E.; Coelho, Mariana N.; Shea, Katriona; Duke, Stephen O. (Springer, 2014)
The invasive thistle Carduus nutans has been reported to be allelopathic, yet no allelochemicals have been identified from the species. In a search for allelochemicals from C. nutans and the closely related invasive species C. acanthoides, bioassay-guided fractionation of roots and leaves of each species were conducted. Only dichloromethane extracts of the roots of both species contained a phytotoxin (aplotaxene, (Z,Z,Z)-heptadeca-1,8,11,14-tetraene) with sufficient total activity to potentially act as an allelochemical. Aplotaxene made up 0.44 % of the weight of greenhouse-grown C. acanthoides roots (ca. 20 mM in the plant) and was not found in leaves of either species. It inhibited growth of lettuce 50%(I-50) in soil at a concentration of ca. 0.5 mg g(-1) of dry soil (ca. 6.5 mM in soil moisture). These values gave a total activity in soil value (molar concentration in the plant divided by the molarity required for 50 % growth inhibition in soil = 3.08) similar to those of some established allelochemicals. The aplotaxene I-50 for duckweed (Lemna paucicostata) in nutrient solution was less than 0.333 mM, and the compound caused cellular leakage of cucumber cotyledon discs in darkness and light at similar concentrations. Soil in which C. acanthoides had grown contained aplotaxene at a lower concentration than necessary for biological activity in our short-term soil bioassays, but these levels might have activity over longer periods of time and might be an underestimate of concentrations in undisturbed and/or rhizosphere soil.
Keywords: Allelochemical; Allelopathy; Aplotaxene; Carduus nutans; Carduus acanthoides; Phytotoxin